PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD AUGMENTED REALITY PADA MATERI SISTEM PEREDARAN DARAH MANUSIA KELAS V SDN SUMBER WARU 1 - Rosi, Fahrur; Ade Cyntia Pritasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a valid, effective, and interesting augmented reality flashcard media for the human circulatory system material for fifth grade students of SDN Sumber Waru 1. The development model used is the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were fifth grade students of SDN Sumber Waru 1. The validation results obtained the following results: (1) media experts 95% (Very Valid), (2) material experts 91.67% (Very Valid), (3) design experts 85% (Very Valid). Effectiveness is reviewed from observations of teacher learning implementation of 90% (effective), students 93% (effective) and evaluation tests of 100% including the classical completion category. Interestingness is reviewed from the teacher response questionnaire of 96.42% (very interesting) and the student response questionnaire of 98.21% (very interesting). Based on these results, the development of augmented reality flashcards is declared valid, effective, and interesting to be used in the learning process.